Transformasi Pendidikan Islam: Kepemimpinan Kepala Madrasah Dan Implementasi Supervisi Efektif - Ani Apiyani (STIKes Ibnu Sina Ajibarang, 2024)
Leadership and leaders are essential to optimize every significant step or activity. Only leaders who are willing to recognize the talents, capacities, initiatives, and good intentions of their followers (people, subordinates, individuals, and groups being led) to take initiative and cooperate can ensure the well-being of the wider community. This type of research is qualitative research, using data collection techniques such as interviews, documentation, and observation. To test the validity of the data, this research employs source triangulation. The results of this research indicate that, as a supervisor, the head of the madrasa is responsible for improving the performance of educational staff. Supervision and control are necessary as tools for educational oversight in the school to ensure alignment with the established goals. The supervisor functions as a preventive measure to avoid deviations and ensure careful task execution. The head of the madrasa conducts supervision of teachers in the learning process through various methods, including classroom visits, guiding teachers in the implementation of the school curriculum, holding meetings, and organizing training sessions.